2003
DOI: 10.1007/s00726-003-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the cerebrospinal fluid of patients with schizophrenia

Abstract: We applied proteomics technologies to analyze the cerebrospinal fluid of patients with schizophrenia. Such an analysis can result in the identification of proteins, which may play a role in the disease progress and thus lead to the discovery of clues of the etiology of schizophrenia. Cerebrospinal fluid from patients and controls was analyzed by two-dimensional gels and the proteins were identified by matrix-assisted laser desorption ionization mass spectrometry (MS) in the MS and MS/MS mode. 54 different gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 29 publications
0
62
0
3
Order By: Relevance
“…146 Interestingly, Thomas et al 147 also reported increased levels of apolipoprotein D in the central nervous system and a decrease in serum of schizophrenia patients, which could imply a compensatory role of apoD for a neuropathological process that is initiated by systemic lipid metabolism insufficiencies. Jiang et al 148 found apolipoprotein A-IV to be downregulated in cerebrospinal fluid of schizophrenia patients. Furthermore, clozapine treatment of rats has been found to alter apoD gene expression.…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…146 Interestingly, Thomas et al 147 also reported increased levels of apolipoprotein D in the central nervous system and a decrease in serum of schizophrenia patients, which could imply a compensatory role of apoD for a neuropathological process that is initiated by systemic lipid metabolism insufficiencies. Jiang et al 148 found apolipoprotein A-IV to be downregulated in cerebrospinal fluid of schizophrenia patients. Furthermore, clozapine treatment of rats has been found to alter apoD gene expression.…”
Section: Apolipoproteinsmentioning
confidence: 99%
“…16 While the literature shows pathology in the structure, function and circuitry of the ACC in schizophrenia, this brain region is not well characterized in the disease state. Proteomics, with the ability to investigate the translation of genomic information together with co-and post-translational modifications, 17 offers an approach to studying the global changes in protein expression and modification caused by neuropathologies such as Alzheimer's Disease (AD), Down Syndrome (DS) and schizophrenia. Previous findings of proteomic investigations into schizophrenia include various proteins associated with metabolism and oxidative stress to be differentially expressed in the prefrontal cortex (PFC) in the disease state relative to controls, 18 proteins previously implicated in schizophrenia as well as some novel proteins to be altered in the frontal cortex, 19 and four of 18 altered proteins in the schizophrenia hippocampus mapping to chromosome 6q.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings of proteomic investigations into schizophrenia include various proteins associated with metabolism and oxidative stress to be differentially expressed in the prefrontal cortex (PFC) in the disease state relative to controls, 18 proteins previously implicated in schizophrenia as well as some novel proteins to be altered in the frontal cortex, 19 and four of 18 altered proteins in the schizophrenia hippocampus mapping to chromosome 6q. 20 In addition, a proteomic study investigating the cerebrospinal fluid (CSF) in schizophrenia identified 54 different gene products, 17 leading to new and refined hypotheses into the molecular mechanisms underlying this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of several CSF proteins were deranged as well, like apolipoprotein A4 [64], complement C3, insulin receptorrelated protein, and vitamin D-binding protein [116]. In a rat model of neuropathic pain, the Ca-binding proteins calmodulin and calretinin as well as protein-tyrosin phosphatase A, Ras-related protein RAB-15, and stress-activated protein kinase JNK3 showed lower levels.…”
Section: Signal Transduction Proteinsmentioning
confidence: 99%
“…Functional imaging and postmortem studies in the brain of patients with these diseases have revealed histological, functional, and neurochemical abnormalities in the anterior cingulated cortex [58][59][60][61][62]. Brain and CSF from patients with schizophrenia as well as brain from animal models of the disorder have been studied by proteomics approaches and a series of proteins possibly related with the disease have been identified [55,[63][64][65][66].…”
Section: Schizophrenia Bipolar Disorder Depressionmentioning
confidence: 99%